Pyramid Scheme Crime: Problems and Oversight in Indonesia - Heru Yuwono, Teguh Basuki; Kharisma, Dona Budi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Investment-based crimes in Indonesia are very high. Data from the Indonesian Financial Services Authority (OJK) in 2023 stated that the total value of public losses due to investment crimes from 2018 to 2022 reached IDR 126 trillion. Various models of investment crimes that are often carried out include illegal futures brokers, illegal investments, forex, and binary options carried out with pyramid schemes or Ponzi schemes. The data indicates that there are problems in handling crimes with pyramid schemes. This research is normative legal research that uses the statute approach method. The legal materials used include primary legal materials and secondary legal materials related to investment crimes. Based on the results of the study, it was found that there are various legal problems in handling crimes with pyramid schemes, including weaknesses in the formulation of regulations. The Trade Law still has limited reach both in terms of subjects and objects which can lead to weak law enforcement. Therefore, it is recommended for relevant stakeholders to reformulate the Trade Law that can accommodate broader subjects and objects.